Regional developments [in 2024 Global Food Policy Report] - Becquey, Elodie; Benin, Samuel; Marivoet, Wim; Gelli, Aulo; Abay, Kibrom A.; Abdelfattah, Lina Alaaeldin; Kurdi, Sikandra; Sarhan, Mohsen; Akramov, Kamiljon T.; Lambrecht, Isabel B.; Pechtl, Sarah; Kishore, Avinash; et al. (International Food Policy Research Institute, 2024)
The regional section of the 2024 Global Food Policy Report examines the evolving problem of malnutrition—including undernutrition, micronutrient deficiencies, and overweight and obesity—in low- and middle-income countries across the world’s major regions. Policy interventions are highlighted that address the particular challenges and opportunities in each region, with recommendations that aim to transform food systems to make healthier, more diverse, and more sustainable diets available, affordable, accessible, and desirable for everyone, including the most vulnerable.